Sociodemographic Factors of Elective and Emergency Cesarean Delivery in the Referal Hospital: A cross-sectional study: Faktor Sosiodemografi pada persalinan seksio sesarea elektif dan emergensi di Rumah Sakit Rujukan: sebuah penelitian potong lintang - Juminten Saimin; Restuaji B.K. Umam; Nur I. Purnamasari; I Putu Sudayasa (Indonesian Socety of Obstetrics and Gynecology, 2022)
Objectives: To analyze the correlation between sociodemographic factors and cesarean section delivery at Referral Hospital in Kendari. Method: This was a cross-sectional study conducted at dr. Ismoyo Hospital in Kendari. Data were obtained from medical records of cesarean section delivery from January to December 2019. Sampling used simple random sampling techniques. Data were analyzed using the Chi-square test. Result: There were 50.5% emergency cesarean and 49.5% elective cesarean. The maternal age was 18-44 years. Most cases are aged 20-35 years (78.5%), have a higher education level (65.1%), employees (53.2%), and multipara (56.5%). There was a correlation between age and cesarean section (p = 0.027). There was no correlation between education level (p = 0.618), occupation (p = 0.563), and parity (p = 0.365) with cesarean section. Conclusion: There is a correlation between maternal age and cesarean section. Education, counseling, and antenatal care should be done for early detection. Keywords: age, cesarean section, education level, occupation, parity